Project-Based Learning Governance on Natural Materials Improving the Creativity of Class VIII Students of SMP Negeri 1 Sigumpar - Siagian, Roy; Sitanggang, Nathanael; Lubis, M. Joharis (Jurnal Pendidikan Matematika dan Sains, 2023)
This research is motivated by the low participation of students of SMP Negeri 1 Sigumpar in participating in the scientific work competition which is their own innovation.    All this time, many people think that the students from the countryside are uncreative and difficult to  make innovation, and also some people think that the students of Junior High School are too early to  start the research.  According to Bloom and Anderson"˜s taxonomy, creative competence is not only for the high school level, but has started even at the elementary school level. By learning to create something out of materials that exist in the surroundings, the construction of the child's thinking will be formed and will be increasingly critical and innovative. Science, Technology, Engineering, and Mathematics (STEM)-based learning really needs to be empowered from an early age.  This is in accordance with the demands for independent learning that the government is currently planning. STEM-based learning makes students free to be creative and apply their ideas and creations.  This research was conducted at SMP N 1 Sigumpar with the aim of finding out whether the application of the project-based learning model on the subject was effective. Nature can be a material for students' innovative work and improve student learning outcomes. The method of this research used a quasi-experimental research design with one group pretest – posttest design. The data collection method that used in this study was a questionnaire, questions and observations in class VIII A as many as 30 students. Data analysis was carried out by descriptive and qualitative.   The results showed that the project-based learning increases student creativity and learning results.  So that this learning method is very good to be applied because based on the experience of students the more enthusiastic about learning.Keywords : Project, Learning, STEM, Creative